(3YbhO GdJhRjY aj GdbGfhf GdOhdj GdNGU (B/ s - (3CMeO SjO MSf eMeO Yajaj s; (3YHOGdefYe ReRe (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3JJfGhd GdQSGdI ehVhYgG aj GdHGH GdChd GdPj jSQO GdEWGQ GdbGfhfj dYbO GdJhRjY, hGdHGH GdKGfj Yf JMOjO GdbGfhf GdhGLH GdJWHjb Ydi YbO GdJhRjY, hGdHGH GdKGdK Yf fWGb GdbGfhf GdhGLH GdJWHjb Ydi YbO GdJhRjY, hCNjQG GdHGH GdQGHY GdPj jJfGhd JShjI efGRYGJ YbhO GdJhRjY(B.s
2017. (3CWQhMI (B((3OcJhQGg(B)-s
(3HHdjhLQGajG(B: (3UaMGJ (B569-585. s
Keywords: (3YbO GdJhRjYs; (3YbO GdJhRjY GdMUQjs; (3YbO GdJhRjY GdGfJbGFjs; (3GdbGfhf GdhGLH GdJWHjb Ydi YbO GdJhRjYs; (3JShjb GdefJLGJs; (3bGfhf GdJMcje GdeUQjs; (3bGfhf GdJMcje GdGfLdjRjs; (3YbO GdHjY GdOhdj ddHVGFYs; (3GdeSFhdjI GdYbOjIs; (3bhGfjf GdHhdjSs; (3GdfXGe GdYGes; (3JShjI efGRYGJ YbO GdJhRjYs; (3GdGNJUGU GdbVGFj GdOhdjs; (3GdJMcje ai YbhO GdJhRjYs; (3dGFMI HQhcSds; (3bGfhf GdJLGQIs; (3GdbGfhf GdOhdj GdNGUs; (3GdbGfhf GdGfLdjRjs; (3YGOGJ GdJLGQI GdOhdjIs; (3GYQGa GdJLGQI GdOhdjIs; (3YbO GdJhRjYs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2017